New strategies for stationary phase integration within centrifugal microfluidic platforms for applications in sample preparation and pre-concentration. Issue 13 (15th February 2017) - Duffy, Emer; Padovani, Rima; He, Xiaoyun; Gorkin, Robert; Vereshchagina, Elizaveta; Ducrée, Jens; Nesterenko, Ekaterina; Nesterenko, Pavel N.; Brabazon, Dermot; Paull, Brett; Vázquez, Mercedes
Abstract : Microfluidic discs integrating silica-C18 and carbon monolithic columns were developed for sample preparation. Abstract : New approaches for fabrication of centrifugal microfluidic platforms (μCDs) for sample micro-extraction and pre-concentration in bioanalytical and environmental applications are presented. The integration of both octadecylsilica (C18) micro-particulate and porous carbon monolithic stationary phases was demonstrated and on-disc extractions of analytes in samples of different nature were performed. A novel strategy based on the packing of micro-particulate stationary phases using porous organic polymer monoliths as column frits was demonstrated through the in situ photo-polymerisation of monolithic frits in a specific area of the micro-channel, thereby greatly facilitating stationary phase packing within μCD platforms. An enrichment factor of 3.7 was obtained for vitamin B12 following on-disc pre-concentration on the octadecylsilica columns. UV-Vis absorbance measurements were also performed in the outlet reservoir permitting quasi-on-line analysis of the small volume fractions collected after extraction, with limits of detection (LODs) found for vitamin B12 (LOD = 43 μM) being rather similar to those found with a commercially available spectrophotometer (LOD = 37 μM). Furthermore, the first integration of carbon monoliths within microfluidic channels is reported. Carbon monoliths were fabricated as rods and cut into discs for their integration within the microfluidic network, offering a highly porous bimodal structure with low flow-through back-pressures, excellent chemical stability as well as adequate mechanical stability. The carbon monolith-based μCD platform was evaluated as a rapid semi-automated pre-concentration approach suitable for in-field use prior to in-lab HPLC quantitation of pollutants at low concentration levels. Calculated mean recoveries for phenol from tap water spiked-samples by using this on-disc pre-concentration method were 68 ± 4% ( n = 4, RSD = 5%).